Influence of surface roughness on cetyltrimethylammonium bromide adsorption from aqueous solution - Wu, Shuqing (Langmuir : the ACS journal of surfaces and colloids, 2011)
The influence of surface roughness on surfactant adsorption was studied using a quartz crystal microbalance with dissipation (QCM-D). The sensors employed had root-mean-square (R) roughness values of 2.3, 3.1, and 5.8 nm, corresponding to fractal-calculated surface area ratios (actual/nominal) of 1.13, 1.73, and 2.53, respectively. Adsorption isotherms measured at 25 °C showed that adsorbed mass of cetyltrimethylammonium bromide per unit of actual surface area below 0.8 cmc, or above 1.2 cmc, decreases as the surface roughness increases. At the cmc, both the measured adsorbed amount and the measured dissipation increased dramatically on the rougher surfaces. These results are consistent with the presence of impurities, suggesting that roughness exacerbates well-known phenomena reported in the literature of peak impurity-related adsorption at the cmc. The magnitude of the increase, especially in dissipation, suggests that changes in adsorbed amount may not be the only reason for the observed results, as aggregates at the cmc on rougher surfaces are more flexible and likely contain larger amounts of solvent. Differences in adsorption kinetics were also found as a function of surface roughness, with data showing a second, slower adsorption rate after rapid initial adsorption. A two-rate Langmuir model was used to further examine this effect. Although adsorption completes faster on the smoother surfaces, initial adsorption at zero surface coverage is faster on the rougher surfaces, suggesting the presence of more high-energy sites on the rougher surfaces